“Factores asociados a recién nacidos pequeños para la edad gestional en el hospital de apoyo N° 2 Yarinacocha, año 2003” - Horna Reategui, Teófilo Juan (2004)
In the present research of type descriptive simple, retrospective, of Court cross, is studied to 118 mothers and their newly born classified as small for her age gestational; at the No. 2 Hospital of support of and arinacocha - Ucayali, from January to December 2003, with the aim of identifying factors associated with this disease. Is analyzed them variables: age maternal, occupation, degree of instruction, State civil, weight to the home of the pregnancy (weight regular), carving maternal, parity, period birth, background personal, background obstetric: abortions, prematurity, low weight to the birth. Maternal diseases, number of prenatal health facility where were antenatal checks, bad habits (number of cigarettes per day, drug use and others), error of date of last menstruation, uterine height and maternal weight gain. Type of termination of pregnancy, sex, weight, size, circumference and APGAR of the newborn,...